Comparison of the accuracy of implant impression by conventional open-tray and digital techniques - Joanna Majid Hayder; Fahd Sudad Ikram (Erbil Dental Journal)
Background and objective: Precision of the impression taken from implants significantly determines the accurate fit of implant-supported prostheses. An imprecise impression may produce prosthesis misfit. This study aimed to evaluate the accuracy of the digital implant impression technique as compared to the conventional technique. Method: A definitive maxillary edentulous model with four implants, two of them 10° anterior-posteriorly angulated, and the other two were parallel implants served as the standard reference for making all the impressions and later for accuracy evaluation. Two groups of ten samples were evaluated, first: open-tray implant impression technique, second; digital implant impression technique. All the models have been saved as standard tessellation language files and converted from 3- Dimensional to 2-Dimensional to calculate the distances between the center of the implants, and the implant angulations measurements by both design programs sketch up, and Auto CAD. Corresponding means for each technique and the definitive reference model were compared by using the t-test test. Results: There was a statistically significant difference between the digital impression technique models and the reference model concerning the distances between the center of the four implants (A, B, C, and D) with p-value of 0.027 and 0.000, respectively. Regarding the angular distortion, there was also a statistically significant difference between the digital and conventional implant impression models with the reference model. Conclusion: It has been concluded that the digital implant impression models in a single angulated implant was more accurate than the traditional open tray models, whereby for a long span, a conventional open tray impression technique is preferable. Keywords: Digital implant impression, Open-tray impression technique, Intra-oral scanner, Abutment level impression.